Productivity and nutritional quality of double purpose sorghum genotypes. - Gutiérrez-Palacios, Nury (2013)
The objective of this study was to evaluate a set of dual purpose sorghum genotypes for their grain and fodder productivity, as well as for nutritional quality of leaves and stems for livestock. From 2003 through 2005, 26, 15 and 8 genotypes were evaluated respectively, in comparison with the control variety INTA CNIA during the postrera season (August to November) in the experimental fields of the National Agricultural Research Centre (INTA CNIA), Nicaragua. Agronomic traits were measured as well as nutritional quality of leaves and stems using the Near Infrared Spectrometry method. For all agronomic and nutritional quality traits were found significant differences among genotypes, except for grain yield in 2004, and the neutral and acid detergent fiber contents in stems. The heritability of agronomic and quality traits in leaves was high (≥ 0.50), with values between 0.96 and 0.51 but lower for most of quality parameters in stems, with values between 0.47 and 0.20. The only significant positive correlation was among crude protein (MAT) and leave – stem ratio in fresh stems (H/RF). The genotypes BF 95-11/195, Sureño, SH 688, V142 and V 144, achieved the best results for grain and fodder yield and fodder quality (regarding both leaves and stems). Sureño out-yielded the control variety for crude protein content per hectare (MPB/ha) in 50 and 33 % for leaves and stems respectively.